Regional boundary conflict of Malaka Regency versus South Central Timor (TTS) regency in lotas segment - Firmina Un Asa; Ajis Salim Adang Djaha; Laurensius P. Sayrani (Review of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: This study discusses the territorial boundary conflict between Malaka Regency and South Central Timor Regency. Research Methodology: This study uses a qualitative method with a case study approach. The dominant forms of analysis carried out in case study research are pattern matching, making explanations and time series analysis. Results: The Boundary Conflict of Malaka Regency and South Central Timor Regency in the Lotas Segment was driven by three factors, namely communication, structure, and personal interests. This conflict causes delays in public services, the dissolution of group unity and damages the relationship and communication between the parties involved in the conflict. Limitations: The limitation of this study is the lack of historical investigation of boundary conflicts between the two conflicting areas. Contribution: This research provides a solution for the relevant local governments to negotiate and mediate so that the conflict does not prolong.